2008
DOI: 10.1108/00251740810846716
|View full text |Cite
|
Sign up to set email alerts
|

Competitive strategy and performance measurement in the Malaysian context

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
133
2
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(166 citation statements)
references
References 92 publications
10
133
2
15
Order By: Relevance
“…The general use of financial measures of performance is consistent with other studies (see for example, Joshi (2001);Phadoongsitthi (2003); Abdel-Kader and Luther (2006);and Jusoh and Parnell (2008). Phadoongsitthi (2003) reported that most Thai firms still focus on financial performance measures such as budget variance analysis, return on investment, cash flow return on investment, and divisional profit.…”
Section: Performance Evaluation Systemssupporting
confidence: 82%
See 1 more Smart Citation
“…The general use of financial measures of performance is consistent with other studies (see for example, Joshi (2001);Phadoongsitthi (2003); Abdel-Kader and Luther (2006);and Jusoh and Parnell (2008). Phadoongsitthi (2003) reported that most Thai firms still focus on financial performance measures such as budget variance analysis, return on investment, cash flow return on investment, and divisional profit.…”
Section: Performance Evaluation Systemssupporting
confidence: 82%
“…Phadoongsitthi (2003) reported that most Thai firms still focus on financial performance measures such as budget variance analysis, return on investment, cash flow return on investment, and divisional profit. Similarly Jusoh and Parnell (2008) revealed that many Malaysian manufacturing firms placed a greater emphasis on financial rather than non-financial measures.…”
Section: Performance Evaluation Systemsmentioning
confidence: 99%
“…Measuring organizational performance was also necessary, and doing so always represents a challenge in strategy-performance studies, as measurement choices can influence findings (Cavalieri, Gaiardelli, & Ierace, 2007;Jusoh & Parnell, 2008;Pongatichat & Johnston, 2008). Performance is an elusive construct and can be evaluated from a narrow, profit-oriented viewpoint or from a broader perspective that also includes considerations such as market share, firm growth, and the attainment of organizational objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Kaplan and Norton (1996) developed a comprehensive performance measurement system known as the balanced scorecard (BSC), a multidimensional approach that includes financial and nonfinancial measures. Because communicating business strategy and aligning individual goals with corporate goals are critical in many organizations, a BSC approach can provide a means for communication and alignment of corporate strategies by cascading and linking measures to each level of organization, including business units, support units, and employees (Jusoh & Parnell, 2008).…”
Section: Assessing Theory and Practice In Competitive Strategy: Challmentioning
confidence: 99%
“…Proponents of using financial measures emphasize the objectivity associated with comparing the performance level of various business units along standardized lines. Although such measures do not result in the valid valuation of intangible assets (Huselid, 1995), financial measures remain a common, widely accepted approach in strategy-performance studies (Jusoh & Parnell, 2008).…”
Section: Assessing Theory and Practice In Competitive Strategy: Challmentioning
confidence: 99%